2014
DOI: 10.1016/j.jnnfm.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A mesoscopic rheological model of moderately concentrated colloids

Abstract: We extend the Maffettone-Minale model by including non-elliptical shapes of dispersed particles, a new family of internal forces controlling particle deformations, and particle-particle interactions. The last extension is made by transposing the way the chain-chain interactions are mathematically expressed in the reptation theory to suspensions. The particle-particle interactions are regarded as a confinement to cages formed by surrounding particles and by introducing a new dissipative motion (an analog of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Subsequently, Grmela et al (2014), advanced a free energy expression specifically to express the surface energy of the droplets. In this free energy expression the surface area was identified with the second invariant of the conformation tensor, which is a reasonable but significant approximation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, Grmela et al (2014), advanced a free energy expression specifically to express the surface energy of the droplets. In this free energy expression the surface area was identified with the second invariant of the conformation tensor, which is a reasonable but significant approximation.…”
Section: Introductionmentioning
confidence: 99%
“…In this free energy expression the surface area was identified with the second invariant of the conformation tensor, which is a reasonable but significant approximation. Despite this improvement, the main problem with the latest Grmela et al (2014) model is that the conformation tensor used is, like b before, identified with square root of the Maffettone & Minale (1998) contravariant conformation tensor, and therefore this is not a contravariant tensor. A further corroborative proof that this is the meaning of the second order tensor used by Grmela et al (2014) is that it has units of length, leading to a second invariant with units of length squared, therefore making the second invariant suitable to represent the ellipsoid surface as they did.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Necessarily this involves introducing parameters for various structure building and breaking phenomena, as well as functional forms relating viscous and elastic material properties to the structure parameter. Such phenomenological parameters can, in principle, be derived by coarse graining the more fundamental, particle micromechanics equations [18,19].…”
Section: Introductionmentioning
confidence: 99%